Analyzing control, capacities, and benefits in Indigenous natural resource partnerships in Canada. (3rd April 2019) - Bullock, Ryan; Boerchers, Morrissa; Kirchhoff, Denis
ABSTRACT: Our work analyzed Indigenous partnership arrangements and conditions associated with natural resource development, specifically, the capacities identified by Indigenous peoples needed to participate in resource wealth generation. The review was needed to take stock of previously understudied and new partnerships emerging in Canada's rapidly growing natural resource sectors where cross-cultural collaboration is becoming a feature, and in some cases a requirement, of new ventures. Results illustrate nine categories of arrangements (i.e., land use/regional planning processes; IBAs; MOUs; Indigenous businesses, joint ventures; environmental assessments; revenue sharing; advisory committees; and regional economic councils) used by Indigenous communities and their partners to assert their control and derive benefits from natural resource extraction. These included highly formal and technical legal arrangements, such as Impact and Benefit Agreements, and less formal arrangements such as Memorandums of Understandings and advisory committees. Using the five capitals' (social, human, financial, built, and natural) approach we also synthesized existing knowledge of partnership capacities and benefits. We found benefits in each of the five capital areas, most of which were forms of human capital. Employment (50%), improved decision making (46%), and also financial support (33%) were the top cited benefits. Results build to the conclusion that differences exist between capacities needed to start working together (pre-existing supporting conditions), and those built through collaboration (new or enhanced capitals as beneficial outcomes). Development models will produce more and sustainable benefits where capacity building is both an explicit process objective and outcome of new partnership designs.